Pengaruh Persepsi Risiko, Kemudahan, Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Secara Online Di Tengah Pandemi - Indah Nuratna Sari; Fendy Maradita (Journal of Management and Business, 2021)
Due to social restrictions during the pandemic, almost all students make online transactions on several e-commerce sites to meet their own needs. This study aims to analyze the effect of perceived risk, convenience, and consumer trust on online purchasing decisions in the midst of the COVID-19 pandemic on Sumbawa University of Technology students. The method used is an associative approach with a sample of 100 respondents obtained by non-probability sampling using purposive sampling technique. The software used in this research is SPSS 20.0. The results in this study indicate that the risk perception variable has a negative and significant effect on online purchasing decisions. Ease has a positive and significant effect on online purchasing decisions. consumer trust has a positive and significant effect on online purchasing decisions. Perceptions of risk, convenience and consumer trust have a simultaneous effect on online purchasing decisions.